2021
DOI: 10.1021/acs.jctc.1c00713
|View full text |Cite
|
Sign up to set email alerts
|

Self-Consistent Auxiliary Density Perturbation Theory

Abstract: The working equations for the extension of auxiliary density perturbation theory (ADPT) to hybrid functionals, employing the variational fitting of the Fock potential, are derived. The response equations in the resulting self-consistent ADPT (SC-ADPT) are solved iteratively with an adapted Eirola–Nevanlinna algorithm. As a result, a memory and CPU time efficient implementation of perturbation theory free of four-center electron repulsion integrals (ERIs) is obtained. Our validation calculations of SC-ADPT stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…As a final test, we have considered that in a recent work from Della Sala group, 15 it has been found that for silver clusters, it is possible to obtain very accurate photoabsorption spectra by using a minimal auxiliary basis set to fit the transition density. So we have directly optimized the exponent of a single 1 s STO function for a collection consisting of only the Ag 20 T d neutral cluster, obtaining a best exponent value equal to 0.40.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a final test, we have considered that in a recent work from Della Sala group, 15 it has been found that for silver clusters, it is possible to obtain very accurate photoabsorption spectra by using a minimal auxiliary basis set to fit the transition density. So we have directly optimized the exponent of a single 1 s STO function for a collection consisting of only the Ag 20 T d neutral cluster, obtaining a best exponent value equal to 0.40.…”
Section: Resultsmentioning
confidence: 99%
“…13 It is worth noting that auxiliary Gaussian-Hertmite functions (named GEN-An GEN-An*) 14 have proven more general as fitting functions, in fact the same set can be used to fit: in SCF both the Coulomb potential and the Fock nonlocal exchange when hybrid functionals are employed, in TDDFT, the perturbed density. 15 At variance, STO functions seem to have quite different requirements depending on the object to be fitted, this should likely ascribed to the cusp at the origin which is retained when the STO products are performed, while for Gaussian the cusp absence, although being unphysical, makes the fitting much easier.…”
mentioning
confidence: 99%
“…Here, the long-range behaviour of the functional used is critical. 279 The polarizabilities of small metal clusters can be significantly influenced by temperature effects. 280 Furthermore, the experimental references for static polarizabilities of such clusters are not always reliable.…”
Section: Density Functional Approximationsmentioning
confidence: 99%
“…Auxiliary function sets of the type GEN-A2* were automatically generated. Analytic Fukui functions and second-order electron binding energies , were computed using auxiliary density perturbation theory. Colored isosurfaces of Fukui functions were prepared using Sinapsis software…”
Section: Computational Detailsmentioning
confidence: 99%